Experimental study of sustainable asphalt mixtures containing waste materials - Mohammed, Humam H. (Edelweiss Applied Science and Technology, 2024)
In the past decade, there has been a significant increase in traffic density and axial load, which has resulted in the road’s rapidly deteriorating condition. Therefore, it was imperative to identify solutions to these issues to enhance the asphalt mixture to withstand excessive loads and weather fluctuations and extend the periodic maintenance period. This research aims to examine the performance characteristics of the asphaltic mixture by incorporating RAP and crumb rubber derived from waste tires and to compare the enhanced and conventional mixtures, regarded as the best sustainable solution the world is currently pursuing. Because crumb rubber is derived from discarded tires, which are difficult to dispose of and cause environmental pollution, this research has incorporated four proportions of crumb rubber (2%, 4%, 6 and 8%) into the 50-60 penetration grade asphalt binder. To achieve the optimal asphalt content and prepare laboratory samples for various laboratory tests, replace 10% of virgin aggregate gradation with RAP using the Marshall method for a wearing course. The outcomes demonstrated the improvement of modified mixtures with crumb rubber contents in the indirect tensile strength (ITS), moisture damage, rutting resistance, and Marshall stability and flow of asphaltic mixes.